MORAL VALUES ANALYSIS ON MAIN CHARACTERS AS SEEN ON “MY SISTER’S KEEPER” FILM BY NICK CASSAVETES - Restu Pitri; Asridayani Asridayani; Sufiyandi Sufiyandi (Universitas Muara Bungo, 2018)
This research analyzes about the moral values found in the film My sister Keeper by Nick Cassavatess. The purposes of this research are to describe kinds of moral values and to describe the good impacts of moral values found in the film My Sister’s Keeper by Nick Cassavatess. In this research, the writer uses descriptive qualitative methods proposed by Creswell (1994) which uses descriptive technique to describe and to analyze the data. The data is analyzed through some ways: identifying, classifying, analyzing and making conclusion. In this research, the writer used theory from Linda and Eyre’s (1997). The results of this research are some kinds of moral value such as honesty, bravery, peace ability, self discipline, respect, kind and friendly, confidence, love and affection, fair and loyalty. The writer also explains the good impact of moral values on the main characters as seen in the film My Sister’s Keeper that Sara Fitzgerald and Anna Fitzgerald has different moral values but after Kate died, the relationship between both of them be better. The most dominant kinds of moral values found in the film My Sister’s Keeper by Nick Cassavetes is Bravery.Key words: Moral Value, Good impact, My Sister’s Keeper